Distribution of heterothallic alleles of Tilletia indica in India - and A.K. SHARMA, J. KUMAR*, J. SHORAN, I. SHARMA, R. AGGARWAL, M.S. SAHARAN (Indian Phytopathology, 2009)
The heterogenous strains of soil borne haploid infective propagules (allantoid sporidia) of Tilletia indica causing Karnal bunt (KB) disease of wheat fuse obligatory in pairs on flower surfaces to establish infection in developing host ovaries. Artificial infection assays using paired monosporidial lines (MLs) in the form of sporulating mycelia raised from haploid allantoid sporidia isolated from teliospores collected from various places in the states of north west India revealed 8 mating types (self incompatibility alleles) in this heterothallic fungal pathogen of wheat. MLs of Haryana and Punjab showed presence of three types of common mating alleles of which only two were noticed in samples of Delhi and Himachal Pradesh. The fourth and fifth alleles traced respectively in MLs of Haryana and Punjab were different from the rest three present in these states. Three alleles conjectured in MLs of Uttranchal were quite different from all five reported above. Representative MLs of 8 alleles when paired in all possible combinations and inoculated on a set of differential lines produced host – pathogen – interaction matrices of 6 distinct pathotypes. Some of these resembled the earlier reported Indian pathotypes. Interestingly, the allele – pair – specificity affected the hostpathogen-interaction matrices of pathotypes yielded by the paired MLs.